2008
DOI: 10.1124/jpet.108.137513
|View full text |Cite
|
Sign up to set email alerts
|

meta-Iodobenzylguanidine, an Inhibitor of Arginine-Dependent Mono(ADP-ribosyl)ation, Prevents Neointimal Hyperplasia

Abstract: The association of ADP-ribosylation with cell proliferation and ischemia-reperfusion injury suggests that it may be a suitable target for therapeutic control of revascularization-induced injury. The purpose of this study was to investigate the inhibitory actions of ADP-ribosylation inhibitors on restenosis. In organ culture, the poly(ADP-ribose) polymerase (PARP) inhibitor 3,4-dihydro-5-methylisoquinolinone (PD128763) was unable to prevent neointimal hyperplasia, whereas the arginine-dependent mono(ADP-ribosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Yau et al (6) hypothesized that mono-ADP-ribosylation enzymes may be associated with the progression of gastric cancer. A previous study (11) has shown that ART1 expression was increased in colorectal cancer and has a positive correlation with the expression of vascular endothelial growth factor (VEGF), which suggests that it may have an association with tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yau et al (6) hypothesized that mono-ADP-ribosylation enzymes may be associated with the progression of gastric cancer. A previous study (11) has shown that ART1 expression was increased in colorectal cancer and has a positive correlation with the expression of vascular endothelial growth factor (VEGF), which suggests that it may have an association with tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the epithelial cells of the respiratory tract and the bronchoalveolar lavage fluid of people with asthma, ART1 may catalyze the mono-ADP-ribosylation of human neutrophil peptide-1 (3), resulting in an inflammatory response. Yau et al (5) demonstrated that meta-iodobenzylguanidine (MIBG), a selective inhibitor of arginine-specific mono-ADP-ribosylation (6), is able to suppress the proliferation and differentiation of vascular smooth muscle cells. The researchers hypothesized that mono-ADP-ribosylation is involved in a Rho-dependent signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Yau et al[44] meta-iodobenzylguanidine (MIBG) was loaded into a fibrin gel for long-term release. MIBG inhibits arginine dependent mono(ADP-ribosyl)ation and might prevent neointimal hyperplasia after angioplasty.…”
Section: Loaded Factor Drug and Vector Systemsmentioning
confidence: 99%
“…Materials used in surgical glues, such as fibrin glue, albumin and urethane, can rapidly form a rigid, hardened structure and also demonstrate good biocompatibility [187189]. Among the available options, fibrin glue has been widely investigated as a carrier for drugs, biological factors, or genes [190194]. Due to its high water uptake and pore-forming abilities, fibrin glue has additionally been studied in the form of tissue engineering scaffolds [195197].…”
Section: Drug Delivery Medical Devices For Soft Tissue Repairmentioning
confidence: 99%